Effects of Electrohydraulic Therapy of Shock Waves on Pain and Lymphedema Measurement Post-Radical Mastectomy (International Journal of Physiotherapy, 2023)
Background: Lymphedema post-mastectomy remains a challenging problem. This study aimed to investigate the efficacy of shock wave electrohydraulic treatment (ESWT) for patients with pain and lymphedema.Methods: Thirty patients (30 women) with pain & lymphedema post-radical mastectomy were evaluated to participate in this Clinical trial. They were recruited from the Minia Cancer Institute- Minia University and Deraya University outpatient clinics. Their ages varied between the ages of 40 and 50 years. They were divided into two groups. Group (1) 'Group of studies': 15 patients seeking ESWT in addition to conventional medical care. Group (2) 'Control group': 15 people seeking conventional medical care only. Patients of the study group (1) were treated with a number of impulses, at least 500 shocks at E2 at 4Hz (equivalent to 0.11mJ/mm square energy). Treatment sessions were delivered twice weekly for six treatments (3 weeks). The assessment used a Visual analogue scale (VAS) for pain and arm circumference midway between the shoulder and elbow for lymphedema measurement.Results: showed that (ESWT) on pain and lymphedema measurement post-radical mastectomy effectively decreased pain as evidenced by the highly significant decreases in the visual analogue scale. These results revealed a substantial VAS reduction (P